US-CHINA COMPETITION AND ASEAN UNITY: WHY ECONOMIC RESILIENCE MATTERS - Wang, Peter Brian M. (AEI Insights, 2025)
Long has ASEAN championed regionalism based on the ASEAN Way i.e., neutrality, consensus, non-interference, inclusivity, non-intervention. Testament to its success is the fact that much of the institutional framework in East Asia - East Asia Summit (EAS), the Asia-Pacific Economic Cooperation (APEC), the ASEAN Plus One mechanisms, ASEAN Regional Forum (ARF), and ASEAN Defence Ministers Meeting Plus (ADMMPlus) – operates along the key principles of the ASEAN Way. However, the ongoing competition between the US and China is upending the liberal world order, and there are concerns that the ASEAN-centred regional order will be impacted as well. Despite China’s or the US’ rhetoric on the matter, the reality is that ASEAN finds itself increasingly side-lined and powerless in the face of rising tensions prompting the belief that ASEAN has been most effective in times of peace, not so much in times of conflict. Moreover, the ongoing conflict has been divisive. Regional powers are realigning themselves with either superpower. Even within ASEAN, the Philippines has strengthened their alliance with the US, compelled to it by China’s growing assertiveness and its own growing exasperation with ASEAN’s lack of support for it, as its members continue to maintain good relations with both China and the US, pursuing their respective national agendas, while cloaking it under ASEAN’s principles of neutrality and non-alignment. Their respective positions largely stem from the complex relationship that individual ASEAN members have with these two great powers. This is certainly reflected in their economic relations with either power. An analysis of trade and investment data finds that the economic relations of ASEAN members with the US and China have strengthened in an unbalanced manner, that leaves ASEAN susceptible to the risk of internal division. One way to address this is by enhancing ASEAN’s resilience, by strengthening economic integration and regional imbalance, thereby enhancing the importance of ASEAN to its members, whether as a market or a source of investments and development. This can contribute to strengthening ASEAN unity and allowing it to take on a more robust and cohesive position on matters of regional importance.